Avaliação da técnica de amamentação das duplas mães/recém-nascidos pré-termo de muito baixo peso ao nascer - Sousa, Ana Lílian Caixeta de Oliveira (2011)
Human milk is the ideal food for the child for several reasons, among them are the nutritional adequacy, protection against infections, better motor and intellectual development and reduction of chronic diseases. However, despite the importance of breastfeeding (BF), when it comes to newborn preterm infants, they face great difficulties in its establishment and continuity. This study aimed to evaluate the breastfeeding technique of preterm infants at discharge, one week, and one month after discharge; to know the rate of breastfeeding of preterm infants at 6 months of chronological age; and the main difficulties faced by mothers during breastfeeding. Participated in this study newborns (NB) with gestational age below 37 weeks and with birth weight less than 1500g, who were discharged between November 15 2008 and November 14 2009, and who were breastfed in the week preceding discharge. The breastfeeding technique was evaluated at discharge, 1 week, and 1 month after discharge, employing the protocol proposed by UNICEF. At these times it was also recorded the weight, the feeding type, and among the children who were not being breastfed it was asked the cause of weaning. At 6 months of chronological age, a telephone contact was made to check the ongoing of BF. Participated in the study a total of 45 pairs of mother/preterm infants. As for the ratings of the breastfeeding technique, due to the peculiarities of preterm newborns, this study found as difficulty factors the drowsiness of the newborn and the empty breasts of mothers, which contributed to the regular and low scores in the aspects Breast Response and Anatomy respectively. One week and one month after discharge and at 6 months of chronological age 81.4%, 48.7% and 23.2% were BF respectively. The average duration of breastfeeding was 80 days and the main difficulties faced by mothers were little milk, difficulty in grip and the refusal of the newborns to accept the mother s breast. Among the pairs who received a regular score at discharge in any of the aspects, only 11.1% remained BF up to 6 months of chronological age, and among those who received a low score in any aspect, none remained breastfeeding, suggesting that the difficulties encountered in evaluating the breastfeeding technique can jeopardize BF and, therefore must be detected so that appropriate measures are taken.